Inverse semigroups with idempotent-fixing automorphisms - Araújo, João (2015)
A celebrated result of J. Thompson says that if a finite group G has a fixedpoint-free automorphism of prime order, then G is nilpotent. The main purpose of this note is to extend this result to finite inverse semigroups. An earlier related result of B. H. Neumann says that a uniquely 2-divisible group with a fixed-point-free automorphism of order 2 is abelian. We similarly extend this result to uniquely 2-divisible inverse semigroups.